2017
DOI: 10.15408/es.v9i2.1402
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Problem Based Learning Model Toward Sains Literacy ‎skill of Student on Reaction Rate Materials

Abstract: This study was aimed to know the effect of problem-based learning model on the ability of students scientific literacy in reaction rate material. Scientific literacy that is examined in this study only on competency dimension of science. This research was conducted at SMAN 8 South TangerangCity. The method used was quasi-experimental with nonequivalent control group design. The sample was taken byusing purposive sampling technique. The data was taken by using an essay test of scientific literacy ability in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, problem-based learning and student-centered learning models can be used to improve students' scientific literacy skills. The results of measuring the effect size of several existing learning models, the learning model that is widely used to encourage students' scientific literacy is the problem-based learning model (Aiman et al, 2019;Firdausi Nuzula & Sudibyo, 2022;Fitriani et al, 2017). Apart from that, the inquiry model is considered effective as a learning model in the classroom because it requires students to think critically, creatively, and analytically to solve problems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, problem-based learning and student-centered learning models can be used to improve students' scientific literacy skills. The results of measuring the effect size of several existing learning models, the learning model that is widely used to encourage students' scientific literacy is the problem-based learning model (Aiman et al, 2019;Firdausi Nuzula & Sudibyo, 2022;Fitriani et al, 2017). Apart from that, the inquiry model is considered effective as a learning model in the classroom because it requires students to think critically, creatively, and analytically to solve problems.…”
Section: Discussionmentioning
confidence: 99%
“…Activity the make participant educate involved direct so that learning will become more meaningful . Besides That after do all learning processes during activity experiment , participants educate will more understand material No just on concept just but capable prove truth from material the(Fitriani, 2015) .Stage fourth ie stage develop and present results work . At stage This participant educate prepare results existing experiments _ obtained and presented the result to front class .…”
mentioning
confidence: 93%
“…Based on study of the International Assessment of Science Learning Outcomes organized by the Organization for Economic Cooperation and Development (OECD) as part from its PISA program , shows that literacy science participant students in Indonesia are lagging behind Far compared to other countries (Fitriani, Milama, & Irwandi, 2017) . The results of the PISA survey in 2012 showed that Indonesia was ranked 64th out of 65 countries with score 382, In 2015 occupied Ranked 64th of 72 with score of 403 , most recently in 2018 it was ranked 70th out of 78 participating countries with acquisition score 396.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation